Oblicz:
c) -2x*(-3xy)=
d) x-x/2 - x/3=
e) -4 * (-x/2) * (- 2x/4)=
g) -(x+1) + (2x+4)=
h) 3(a kwadrat - 4)-(-a kwadrat+ 2)=

a)(x+3)(x-7)=
b) -3(2x-1)(x+6)=
c) -(y-1)(2y+4)=
d) 2a kwadrat - (a+6)(2a-1)=
e) 3(x kwadrat - 1)-(x-3)(x+2)=
z góry dzięki :)

3

Odpowiedzi

2009-10-07T16:26:27+02:00
Najlepsza Odpowiedź!
2009-10-07T16:35:11+02:00
C) -2x*(-3xy)=6x^2y
d) x-x/2 - x/3=
e) -4 * (-x/2) * (- 2x/4)=
g) -(x+1) + (2x+4)=-x-1+2x+4=3x+3
h) 3(a kwadrat - 4)-(-a kwadrat+ 2)=3a^2-12+a^2+2=-9a^2+2

a)(x+3)(x-7)=x^2+3x-7x-21=x^2-4x-21
b) -3(2x-1)(x+6)=-(6x+6)*(x+6)=6x^2+6x+36x+36=6x^2+42x+36
c) -(y-1)(2y+4)=-2y^2-2y-4y-4=2y^2-6y-4
d) 2a kwadrat - (a+6)(2a-1)=2a^2-2a^2+12a-a-6=11a-6
e) 3(x kwadrat - 1)-(x-3)(x+2)=3x^2-3-x^2-3x+2x-6=2x^2-x-6
z góry dzięki :)
2009-10-07T18:39:18+02:00
A)(x+3)(x-7)=x^2+3x-7x-21=x^2-4x-21
b) -3(2x-1)(x+6)=-(6x+6)*(x+6)=6x^2+6x+36x+36=6x^2+42x+36
c) -(y-1)(2y+4)=-2y^2-2y-4y-4=2y^2-6y-4
d) 2a kwadrat - (a+6)(2a-1)=2a^2-2a^2+12a-a-6=11a-6
e) 3(x kwadrat - 1)-(x-3)(x+2)=3x^2-3-x^2-3x+2x-6=2x^2-x-6